A Discussion on Corruption and Political Risks in Latin American Countries - a General View Using Chaos Theory - Filipe, J.; Ferreira, M. A. M. (EasyChair Preprint Nº 7939, 2025)
Along this chapter, a general view over political risks and corruption is given, analyzing the way these phenomena distort the economies. Chaos Theory is used to show social instability and disorganization effects in economies development. The consequences in developing countries socioeconomic structures are complex as much as there are dynamic interactions with a complex effects net in systems. This issue is studied having by reference Latin American countries, where corruption is easily understood as a phenomenon that much distorts these countries development. Historically, in general, these countries have great potential to make business and to receive foreign investments, being potentially attractive to companies. Anyway, political risks and corruption are seen as serious obstacles when investments are studied in terms of business attractiveness. In recent years, corruption is perceived as being increasing, creating a brake to development and to stability on these socio-economic systems. In literature, chaos theory has been applied recently also, particularly, in the politics context. A reflection on chaos theory in dynamical systems is made to understanding political issues and corruption. Some events in the political context in Latin American countries are considered. Macro-strategic ideas of states positioning in the international stage are also taken in account. Following this argumentation, the “Drop of Honey Effect” metaphor is applied, somewhat parallel to that of “Butterfly Effect”. “Drop of Honey Effect” is considered to be more suited to portray social phenomena and in this particular case to political phenomena, than the “Butterfly Effect”.